2015
DOI: 10.1590/s1413-70542015000400011
|View full text |Cite
|
Sign up to set email alerts
|

RICE PARBOILING WASTEWATER IN THE MAXIMIZATION OF CAROTENOIDS BIOPRODUCTION BY Phaffia rhodozyma

Abstract: The interest in carotenoid production from natural sources has increased based in their possible use as dyes and their powerful biological antioxidant capacity. This study evaluated the use of rice parboiling wastewater (RPW) as an alternative substrate for the bioproduction of carotenoids using the yeast Phaffia rhodozyma and found it to be promising as the only source of nutrients, reaching a concentration of 0.6 μg mL -1 (259.1 μg g -1 ) in 48 h. To increase the potential use of this industrial effluent, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 20 publications
0
13
0
3
Order By: Relevance
“…It was incubated at 25 °C, 150 rpm for 48 h or the period of time needed to reach 1×10 8 cel.mL , counted by the Neubauer chamber (Rios et al, 2015). Bioproduction of carotenoids was carried out in 500 mL Erlenmeyer flasks with 153 mL YM production medium, at initial pH of 6.0, and 10% inoculum (10 8 cel.mL -1…”
Section: Production Of Carotenoidsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was incubated at 25 °C, 150 rpm for 48 h or the period of time needed to reach 1×10 8 cel.mL , counted by the Neubauer chamber (Rios et al, 2015). Bioproduction of carotenoids was carried out in 500 mL Erlenmeyer flasks with 153 mL YM production medium, at initial pH of 6.0, and 10% inoculum (10 8 cel.mL -1…”
Section: Production Of Carotenoidsmentioning
confidence: 99%
“…The operating conditions of the process were 25 °C, 180 rpm for 168 h (Rios et al, 2015). The resulting biomasses were dried in an oven at 35 °C for 24 h. Then, they…”
Section: Production Of Carotenoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rios et al (16) observed positive eff ects of the increase in malt extract concentration on carotenoid production but not of the yeast extract concentration when using P. rhodozyma in similar culture media without the use of raw glycerol. The yeast extract and other nutrients added to the culture medium did not infl uence the production of carotenoids by Xanthophyllomyces dendrorhous ENM 5 at 20 °C and 250 rpm.…”
Section: Eff Ect Of the Culture Medium Composition On Carotenoid Prodmentioning
confidence: 99%
“…In a previous study carried out by our research group, the production of carotenoids by the wild yeast Sporidiobolus pararoseus with the use of a complex medium containing by-products such as raw glycerol, corn steep liquor and sugar cane molasses was investigated (15). The production of carotenoids from Phaffi a rhodozyma NRRL Y-17268 was investigated in a culture medium containing pure glycerol and raw glycerol as additional carbon sources (8) and parboiled rice effl uent as nitrogen and phosphorus sources (16). Moreover, carotenoids produced by this yeast strain had antioxidant activity (expressed as Trolox equivalent) of 4.00 and 3.66 mM/μg in ABTS radical cation discoloration and ferric reducing antioxidant power assays, respectively (17).…”
Section: Introductionmentioning
confidence: 99%